PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, PENEKANAN ANGGARAN, DAN KOMPLEKSITAS TUGAS TERHADAP KESENJANGAN ANGGARAN - Ni Luh Mutia Putri; Cokorda Gde Bayu Putra (UNHI Press, 2022)
Budget slack is the difference between the reported budget report and the budget that is not in accordance with the best entities of an organization. This study aims to examine how the influence of budgetary participation, budget emphasis, and task complexity on budget gaps. The population in this study were all employees in the SKPD Tabanan Regency. This research is quantitative and meanwhile the sample technique used is purposive sampling, with this the research sample produced is a total of 57 employees. The analytical method used in this research is multiple linear regression analysis. The hypothesis was tested using t-test with a significance level of 5%. Based on the results of the analysis test simultaneously the influence of budgetary participation, budget emphasis, and task complexity significantly affect the budget gap, and partially the influence of budgetary participation, budget emphasis, and task complexity have a positive and significant effect on the budget gap.